An Analysis of the Gap Between Data Protection Regulations and Privacy Rights Implementation in Indonesia - Judijanto, Loso; Solapari, Nuryati; Putra, Irman (Eastasouth Institute, 2024)
This paper analyzes the gap between data protection regulations and the implementation of the right to privacy in Indonesia from a juridical normative perspective. Despite the enactment of the Personal Data Protection (PDP) Law in 2022, significant challenges remain in ensuring the protection of personal data. These challenges include vague legal definitions, limited enforcement mechanisms, and insufficient provisions for regulating emerging digital technologies such as artificial intelligence and big data. Additionally, public awareness of privacy rights remains low, further exacerbating the ineffective implementation of the law. Through a comparative analysis with international frameworks like the GDPR, this paper highlights key areas for improvement in Indonesia's data protection landscape. Recommendations include establishing a centralized data protection authority, enhancing legal provisions for technological advancements, and increasing public engagement to ensure the effective protection of privacy rights in the digital age.